EFFECTIVE CALLUS INDUCTION AND PLANT REGENERATION IN THE CULTURES OF HYDROCERA TRIFLORA WIGHT & ARN. (International Journal of Food and Nutritional Sciences, 2021)
In this study we report the development of effective in vitro systems for callus induction and mass propagation of Hydrocera triflora. Explants were collected from its natural habitat to derive plantlets through in vitro technique. Morphogenetic potential of somatic explants like shoot tip, axillary bud and leaf discs were studied by culturing them on Murashige and Skoog’s medium, either alone or in combinations, with various plant growth regulators namely benzyl amino purine, indole-3-acetic acid, naphthalene acetic acid, kinetin and 2, 4-dichlorophenoxyaceticacid. Inoculated shoot tips and axillary bud explants expressed 100% shoot growth as well as multiple shoot formation with BAP+IAA (2.5mg/l each) treatment. Inoculated leaf disc explants shown significant callus initiation. Further caulogenesis and rhizogenesis were also noticed. The shoots rose from shoot tip and axillary bud explants were transferred to rooting medium containing the combinations of BAP+IAA, IAA+NAA and KIN+NAA to enhance root formation. Among, BAP+IAA and KIN+NAA combinations seems to be an effective for rhizogenesis with 100% rooting response. 2,4-D was reported as an effective hormone for callus initiation. The plantlets regenerated were acclimatized and propagated successfully.